(3Jbhje HWGbGJ GddZI GdYQHjI aj Ua GdQhVI GdKGfjI aj GdeOGQS GdQSejI aj VGMjI HjQhJ GdLfhHjI ddYGe GdOQGSj (B2007-2008s - (3Rjf GdOjf, fHjdI cQes ((3HjQhJs (3LGeYI GdbOjS jhSas, 2008)
(3JgOa GdOQGSI GdMGdjI Edi Jbhje HWGbGJ GddZI GdYQHjI aj Ua GdQhVI GdKGfjI aj GdeOGQS GdQSejI aj VGMjI HjQhJ GdLfhHjI, hPdc ef NdGd GSJWdGY BQGA GdeOjQjf (B((3GJ(B) (3hGdeYdeGJ GddhGJj jOQSf aj Ua GdQhVI GdKGfjI(B. (3hdJMbjb eG SHb GYJeOJ GdOQGSI Ydi GdefgL GdhUaj ceG Je EYOGO GSJHGfI ehMOI ehLgI dCaQGO YjfI GdOQGSI GdJj TedJ GdeOjQjf(B((3GJ(B) (3aj Ua GdQhVI GdKGfjI aj GdeOGQS GdQSejI aj VGMjI HjQhJ GdLfhHjI GdJj HdZ YOOgG (B13 (3eOQSI eeG jYGOd (B13 (3eOjQkG, cPdc JVefJ GdYjfI GdeYdeGJ GddGJj jOQSf HWGbGJ GddZI GdYQHjI dUa GdQhVI GdKGfjI aj GdeOGQS YjfI GdOQGSI hHdZ YOOgf (B85 (3eYdeI(B. (3HYO eYGdLI GdHjGfGJ aj VhA GdJbOjQGJ GdJbhjejI ddeOjQjf (B((3GJ(B) (3hGdeYdeGJ(B/ (3haj VhA eJZjQj GdOQGSI, CSaQJ GdfJGFL Yf GdBJj(B: (3habkG deJZjQ GdNHQI; JHjf Cf YOO GdabQGJ GdJj MUOJ GdJbOjQ GdYGdj GdeGdj HdZ (B20 (3abQI, ef ELeGdj GdGSJHGfI GdHGdZ YOOgG (B84 (3abQI, Cj Cf GdfJjLI LGAJ YGdjI HfSHI (B23%. (3jdGMX cPdc ef GdfJGFL Cf ELeGdj GdabQGJ GdJj fGdJ JbOjQkG eJhSWkG (B39 (3abQI ef ELeGdj abQGJ GdGSJHGfI, Cj GdfJjLI LGAJ eJhSWI(B. (3hjJVM CjVkG ef GdfJGFL Cf ELeGdj GdabQGJ GdJj CMQRJ JbOjQkG eJOfjkG (B25 (3abQI ef ELeGdj abQGJ GdGSJHGfI, Cj GdfJjLI LGAJ eJOfjI(B. (3CeG habkG deJZjQ GdeDgd GdYdej, ajJHjf Cf YOO GdabQGJ GdJj MUOJ GdJbOjQ GdeJhSW HdZ (B45 (3ef ELeGdj abQGJ GdGSJHGfI Cj Cf ELeGdj GdabQGJ GdJj CMQRJ GdJbOjQ GdeJOfj HdZ (B19 (3abQI ef ELeGdj abQGJ GdGSJHGfI, Cj Cf GdfJjLI LGAJ eJOfjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Banlieu du Sud; Public Sector Kindergarten Arabic Language education School Evaluation; Secteur Public Maternelle L$1 (Benseignement de la langue Arabe Evaluation Scolaires; South of Beirut; (3GdJYdje GdQSej QjGV GdCWaGd JYdje GddZI GdYQHjI GdJbjje GdeOQSjs; (3GdVGMjI GdLfhHjIs